Efeitos citotóxicos de flavonoides metoxilados extraídos da Solanum Paludosum e seus mecanismos de ação sobre a linhagem de gliobastoma humano (GBM-02), in vitro - Oliveira, Marcela de Almeida Rabello (2018)
Glioblastoma (GBM) is the most malignant brain tumor, incurable and highly resistant to drug treatment. Solanum paludosum Moric is a species belonging to the Solanaceae family, whose antioxidant, vasorelaxing and molluscicidal effects have already been described in the literature. In this work, we verified the antitumor effects of flavonoids extracted from S. paludosum on human GBM cell line (GBM02). Three flavonoids were selected which showed greater activity on the reduction of cell viability of GBM02, as well as the flavonoid fraction from which they were isolated. These flavonoids resemble structurally with gossypetin and kaempferol, however, presenting different methoxyl substitutions. The three flavonoids (Sp1, Sp2 and Sp3) and the flavonoid fraction induced a typical morphological pattern of cell death, especially Sp1 and Sp2. To investigate a possible cause for these effects, we analyzed the lipid peroxidation processes through the analysis of the malondialdehyde (MDA) marker and the activity of the human enzyme topoisomerase II-α (TOPO II-α), through the topological analysis of the kDNA plasmid by electrophoresis. We demonstrated that the treatments induced an increase in MDA levels, characteristic of the lipid peroxidation process, and showed inhibitory activity on TOPO II-α. We verified through the cell cycle analysis the increase in the cell ratio in G0/G1 and a reduction in S/G2/M and, finally, we demonstrated a reduction in cellular mobility through the scratch assay and the organization of the actin filaments. We concluded that the treatments initially inhibited the enzyme TOPO II-α and induced permanent damage in the DNA, causing cell cycle arrest in G0/G1 before enter apoptosis, reason why they reduced the migratory capacity. The literature indicates that the flavonoid methylation process reduces its anti-oxidant capacity; therefore, the lipid peroxidation process possibly occurred due to apoptosis induced by irreparable DNA damage. The Sp1 and Sp2 flavonoids and the fraction had cytotoxic effects on GBM02 higher than the standard drug temozolomide, demonstrating the potential to be used as structural models for the design of new antitumor lead compounds.